2018
DOI: 10.1038/s41467-018-04693-9
|View full text |Cite
|
Sign up to set email alerts
|

Computational design of high-performance ligand for enantioselective Markovnikov hydroboration of aliphatic terminal alkenes

Abstract: Finding optimal chiral ligands for transition-metal-catalyzed asymmetric reactions using trial-and-error methods is often time-consuming and costly, even if the details of the reaction mechanism are already known. Although modern computational analyses allow the prediction of the stereoselectivity, there are only very few examples for the attempted design of chiral ligands using a computational approach for the improvement of the stereoselectivity. Herein, we report a systematic method for the design of chiral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(51 citation statements)
references
References 49 publications
1
50
0
Order By: Relevance
“…Then, we tested the C 2 -symmetrical P-chirogenic bisphosphine ligand (S,S)-QuinoxP* in the copper(I)-catalyzed enantioselective borylation of racemic 1a (Scheme 2). [16] We began investigating the impact of steric congestion in quadrant III on the enantioselectivity.T he ligands were constructed by combination of chiral (CP)a nd achiral (AP)phosphine modules.The combination of bulkier chiral phosphine modules [(S)-CP2 and (S)-CP3]r elative to the module bearing a tert-butyl group [(S)-CP1]and adi-tertbutyl phosphine module (AP1)d ecreased and inverted the enantioselectivity.T he reactions with ligands bearing either an adamantyl or a tert-octyl group in quadrant III,that is,(S)-Quinox-AdtBu 2 and (S)-Quinox-tOct-tBu 2 ,r esulted in low enantioselectivities [(S)-Quinox-tBu 3 :7 3%,1 7% ee;( S)-Quinox-AdtBu 2 :73%, À7% ee;(S)-Quinox-tOct-tBu 2 :62%, À3% ee]. In contrast, we found that the reaction with the three-hindered-quadrant chiral bisphosphine ligand (S)-Quinox-tBu 3 smoothly proceeded to selectively furnish (S)-3a in high yield, albeit with low enantioselectivity [73 %yield, 17 % ee for (S)-3a; < 10 % yield for 4].…”
Section: Resultsmentioning
confidence: 99%
“…Then, we tested the C 2 -symmetrical P-chirogenic bisphosphine ligand (S,S)-QuinoxP* in the copper(I)-catalyzed enantioselective borylation of racemic 1a (Scheme 2). [16] We began investigating the impact of steric congestion in quadrant III on the enantioselectivity.T he ligands were constructed by combination of chiral (CP)a nd achiral (AP)phosphine modules.The combination of bulkier chiral phosphine modules [(S)-CP2 and (S)-CP3]r elative to the module bearing a tert-butyl group [(S)-CP1]and adi-tertbutyl phosphine module (AP1)d ecreased and inverted the enantioselectivity.T he reactions with ligands bearing either an adamantyl or a tert-octyl group in quadrant III,that is,(S)-Quinox-AdtBu 2 and (S)-Quinox-tOct-tBu 2 ,r esulted in low enantioselectivities [(S)-Quinox-tBu 3 :7 3%,1 7% ee;( S)-Quinox-AdtBu 2 :73%, À7% ee;(S)-Quinox-tOct-tBu 2 :62%, À3% ee]. In contrast, we found that the reaction with the three-hindered-quadrant chiral bisphosphine ligand (S)-Quinox-tBu 3 smoothly proceeded to selectively furnish (S)-3a in high yield, albeit with low enantioselectivity [73 %yield, 17 % ee for (S)-3a; < 10 % yield for 4].…”
Section: Resultsmentioning
confidence: 99%
“…The P‐chirogenic chiral bisphosphine ( S , S )‐QuinoxP* has been recognized as a high‐performance chiral ligand for various transition‐metal‐catalyzed reactions . Our group has developed a method for the modular synthesis and systematic modification of such quinoxaline‐based bisphosphine ligands (QuinoxP*‐type ligands) . This design strategy allows easy modification of the alkyl motifs on the phosphorus atoms, thus enabling quadrant‐by‐quadrant structure modulations.…”
Section: Introductionmentioning
confidence: 99%
“…The regioselectivity reduced from excellent (2w, 2x) to good (2y), and then to moderate (2z, 2aa), when the alkyl substituent was changed from 3 to 2 and to 1, respectively. In contrast, for the Cu-and Rhcatalyzed versions, 1 alkyl substituted alkenes usually gave good regioselectivities, whereas 2 and 3 alkyl substituted alkenes reacted with lower regioselectivities [9][10][11][12][13] . Furthermore, the reaction tolerated a variety of functional groups, including phenyl ether (2a, 2e-h), benzyl ether (2b, 2c), silicon ether (2d), fluoro (2e), trifluoromethyl (2f), trifluoromethoxy (2g), phenylborate (2h), sulfonamide (2l), amide (2m, 2q, 2r), amine (2u), thioether (2n), sulfone (2o), and ketone (2p) groups, as well as some pharmaceutically important cycles, such as indole (2i), furan (2r), cyclopropane (2q), and amantadine (2v, 2w).…”
Section: Resultsmentioning
confidence: 90%
“…Fe(OTs)3 was shown to be a better iron source than FeCl2 (entry 8). Notably, both the anion and cation in the base play important roles in determining the yield and regioselectivity (entries [8][9][10][11][12], which suggests the involvement of an iron alkoxide ate as a key catalytic intermediate 15f, 16 , and the steric effect was indicated to have an important impact on the regioselectivity (entries [8][9][10]. Lastly, the reaction proceeded with undiminished yield and regioselectivity using high-purity FeCl2 (99.99%) (entry 13), while the use of other metal chlorides (copper, nickel, cobalt, and palladium) led to low reactivities and to the formation of the product with anti-Markovnikov regioselectivity (entries 14-17).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation